HUBUNGAN ANTARA PENGARUH MEDIA BERUNSUR AGRESIF TERHADAP TINGKAH LAKU LANGSANG PELAJAR TINGKATAN 4 DAN 5 - Muhammad Zamri, Nur Aqilla Natasha; Kamarul Arifain, Siti Marhamah (Jurnal ’Ulwan, 2023)
Criminal activities that often occur among teenagers are caused by aggressive media. This study aims to examine the influence of aggressive media on the casual behavior of students form 4 and 5 at SMK Seri Perak. This study was using a quantitative survey method. A total of 118 students were selected to be respondents of the study among students in form 4 and form 5. This study using three questionnaires which is demographic information, General Aggression Model questionnaire by Anderson and Dill (2002) and The Effect by Violent Media On Aggression questionnaire by Buss and Perry Aggression Questionaire (1992). The data obtained was analyed using Statistical Package For Social Science, Version 25.0 (SPSS) software. The results of the study found that there was a significant relationship between the influence of aggressive media on students aggressive behavior. In addition, the findings of the study also show that there was no significant difference between promiscuous behavior among form 4 and form 5 students based on race, gender and grade level. Therefore, this study is expected to be able to help the school authorities, government authorities especially parents in dealing with the problem of student misbehavior.